Time-parallelisation techniques with applications to plasma simulation - Danieli, F (2021)
Parallel-in-time (PinT) methods have become an increasingly popular tool in the numerical solution of time-dependent Partial Differential Equations (PDEs), in light of their potential for extracting additional concurrency when spatial parallelism saturates. Particularly complex applications, such as the ones involving plasma simulations for fusion research, would benefit greatly from the implementation of such methods, given the large computational time usually necessary for the numerical solution of their governing equations.